Aid and sectoral labour productivity - Pablo Selaya; Rainer Thiele (Kiel Institute for the World Economy (IfW), 2008)
The paper examines empirically the proposition that aid to poor countries is detrimental for external competitiveness, giving rise to Dutch disease type effects. At the aggregate level, aid is found to have a positive effect on growth of labour productivity. A sectoral decomposition shows that the effect is significant and positive both in the tradables and the nontradables sectors. The paper thus finds no empirical support for the hypothesis that aid reduces external competitiveness in developing countries. Possible reasons are the existence of large idle labour capacity and high levels of dollarization in financial liabilities at the firm level.
Keywords: F35; O47; 330; Foreign aid; sectoral labour productivity; Dutch disease; Entwicklungshilfe; Wirtschaftspolitische Wirkungsanalyse; Arbeitsproduktivität; Wirtschaftswachstum; Dutch Disease; Internationaler Wettbewerb; Entwicklungsländer